Primêre leerlinge se geskiedenispotentiaal: 'n empiriese ondersoek na senior primêre leerlinge en onderwysers se vermoë om indringende vrae oor 'n historiese gebeurtenis met begrip en insig te beantwoord - Hattingh, Johannes Hendrik (Rhodes University, Faculty of Education, Department of Education, 1989)
The main aim of this research was to determine the potential of senior primary pupils and serving teachers to understand a text that is concerned with a historical event. A test was written by 136 white standard 3, 4 and 5 pupils from a Cape Province primary school, as well as 32 serving teachers from various other Cape Province primary schools. The test consisted of a text and questions based upon it. The testees had 60 minutes at their disposal to study the text and give written answers to the questions. The historical event explained in the text dealt with the Peasant Uprising that occurred in England in 1381. Eight open-ended questions were asked. The questions were graded according to difficulty and based on the model of Merrit to test the following levels of thought: knowledge, application, inference and evaluation. In the dissertation attention is paid to the following aspects: 1. Background for the research. 2. The most important theoretical aspects that play a role in the process of historical understanding. 3. A statistlcal analysis of the results obtained from the pupils and teachers, with attention to those factors that may have influenced the results e.g. verbal IQ, age, interest, etc. 4. The quality of the teachers' and pupils' answers as well as examples from their work to illustrate certain aspects. 5. The most important conclusions that can be drawn from the research. Based on their answers to the graded questions the pupils were grouped into different levels to ascertain whether a significant pattern would emerge for each standard. It became clear, however, that irrespective of age or verbal IQ the pupils could not consistently be grouped into a specific level or category. The most important conclusions of the research are the following: 1. The ability of senior primary pupils to cope with intellectually stimulating material are underestimated. 2. A variety of factors influenced the results of the pupils, but not one of the factors studied in this research was found to be of significant importance. 3. The average primary teacher do have the potential ability to cope with more difficult historical material than the present factual approach would suggest.
Keywords: History -- Study and teaching (Elementary)